2012
DOI: 10.1089/scd.2010.0507
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity in Stem Cell Antigen-1 KO Mice

Abstract: Stem Cell Antigen-1 (Sca-1) is a member of the lymphocyte-activated protein 6 family and has served as a marker for the identification of stem cells in various tissues, including fat depots. In vitro and in vivo studies suggest the possible involvement of Sca-1 in adipogenic differentiation and link Sca-1 antigenicity with adipocyte progenitors. Previously, we showed that Sca-1-enriched populations of ear mesenchymal stem cells possess enhanced capacity to differentiate into adipocytes. Additionally, we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Sca1 (Ly6a) is highly expressed in pro-adipogenic mesenchymal stem cells (Staszkiewicz et al, 2008); however, the gene targeting of Sca1 in mice did not cause a significant change in adipose tissue size (Staszkiewicz et al, 2012). These findings suggest that Sca1 serves as a useful cell surface marker to identify pro-adipogenic ASCs; however, Sca1 itself may not play a substantial biological role in the regulation of adipose tissue size and function.…”
Section: Discussionmentioning
confidence: 99%
“…Sca1 (Ly6a) is highly expressed in pro-adipogenic mesenchymal stem cells (Staszkiewicz et al, 2008); however, the gene targeting of Sca1 in mice did not cause a significant change in adipose tissue size (Staszkiewicz et al, 2012). These findings suggest that Sca1 serves as a useful cell surface marker to identify pro-adipogenic ASCs; however, Sca1 itself may not play a substantial biological role in the regulation of adipose tissue size and function.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, Friedman and colleagues pioneered an elegant cell sorting strategy to identify and isolate a rare, but highly adipogenic progenitor population capable of differentiating into functional adipocytes both in vitro and in vivo (Rodeheffer et al, 2008). However, the markers utilized (Sca-1, CD24 and CD34) are not individually specific for the adipose lineage, and some are functionally dispensible for the initial formation of adipose progenitors (Staszkiewicz et al, 2011). In addition, the molecular identity and gene expression program of primary committed preadipocytes from different depots remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry analysis has revealed that the stem cell/precursor cell population in the SVF of mice fat depots is Sca-1 positive [ 10 , 14 ]. Our previous in vitro studies showed that Sca-1 positive cells isolated/sorted from either ear mesenchymal stem cells (EMSC) or SVF of fat depots displayed robust adipogenic potential [ 16 , 17 ]. In contrast, our in vivo experiments showed only subtle metabolic disorders (glucose intolerance, insulin resistance) between Sca-1 KO and wild type mice [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous in vitro studies showed that Sca-1 positive cells isolated/sorted from either ear mesenchymal stem cells (EMSC) or SVF of fat depots displayed robust adipogenic potential [ 16 , 17 ]. In contrast, our in vivo experiments showed only subtle metabolic disorders (glucose intolerance, insulin resistance) between Sca-1 KO and wild type mice [ 17 ]. We did not detect either a defect in adipogenic tissue development or an increase in fat mass content between Sca-1 KO and wild type mice in an obesogenic environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation